Blunted cardiovascular reactivity may serve as an index of psychological task disengagement in the motivated performance situations - Maciej Behnke (Nature Portfolio, 2021)
Abstract Challenge and threat models predict that once individuals become engaged with performance, their evaluations and cardiovascular response determine further outcomes. Although the role of challenge and threat in predicting performance has been extensively tested, few studies have focused on task engagement. We aimed to investigate task engagement in performance at the psychological and physiological levels. We accounted for physiological task engagement by examining blunted cardiovascular reactivity, the third possible cardiovascular response to performance, in addition to the challenge/threat responses. We expected that low psychological task engagement would be related to blunted cardiovascular reactivity during the performance. Gamers (N = 241) completed five matches of the soccer video game FIFA 19. We recorded psychological task engagement, heart rate reactivity, and the difference between goals scored and conceded. Lower psychological task engagement was related to blunted heart rate reactivity during the performance. Furthermore, poorer performance in the previous game was related to increased task engagement in the subsequent match. The findings extend existing literature by providing initial evidence that blunted cardiovascular reactivity may serve as the index of low task engagement.